(untitled) (Altre Modernità, 2009)
The marks of the events on the urban landscape are a city’s writing. More than writings on a city - amongst which are the memorable work of Baudelaire, the ";flâneur";, and Apollinaire’s Lettre-Océan - they represent the analysis of the city that writes on its own texture. This phenomenon relies on a procedure of diversion and estrangement which turns famous places into uncommon areas and it finds amongst its founding models the cinematographic production of Francois Truffaut (Fahrenheit 451). A similar approach allows us to capture the significance of the work of Dominique Fourcade, one of the most important contemporary French poets. In MW Chute, a poem dated 5th October 2001, he describes the horror of the collapse of New York City’s twin towers. In this piece, Fourcade describes what happened to him on 9/11 not much from a man’s perspective but rather from . a poetic standpoint. Ground Zero allows his writing to jump forward, and turn into a verbal city and labyrynth. His reflections on the urban landscape which, collapses under the explosion become a map of dispersed images made of innumerabile détournements (detour aheads), of endless variants and deviations. The event becomes the model and shape of his writing.